Propriedades de transporte eletrônico em filmes de diamante crescidos por deposição de vapores químicos - Berengue, Olivia Maria (2007)
In this work it was investigated some fundamental properties of undoped and Borondoped (p-type) synthetic diamond films. It was investigated the influence of the cleaning process on the surface s quality in order to produce better metal-diamond electrical contacts. Two cleaning processes were used: chemical and physical (thermal treatment). The Raman spectroscopy was used as a fundamental tool in order to quantify the changes in the samples surfaces after both treatments. It was observed an increase of the resistivity, and consequently a decrease of the superficial conductivity. This fact was related to non-diamond layers remotion being confirmed by current-voltage measurements. These curves show the Space Charge Limited Currents (SCLC) as the dominant conduction process in the samples revealing the expected insulator character of the undoped films. It was also investigated the presence of charge localization eﬀects (due to the presence of deep levels) using the admittance spectroscopy. It was found two impurity centers with activation energies around 34-74 meV and 340-360 meV. They are related to the activation of non-Boron deep levels and Boron acceptors, respectively. The most important conclusion in this case is that the presence of these levels suggests diﬀerent conduction mechanisms acting on the samples; this hypothesis was confirmed by temperature dependent resistivity measurements. Moreover, it was confirmed the hopping process as the dominant conduction mechanism in a large range of temperatures. Additionally, it was determined the spatial extension of the wave function associated to the carriers. All these previous data on the transport mechanisms in diamond films have motivated the development of a device which was primarily designed to be used as a temperature sensor. Characteristics such as sensibility, resolution and time response were well determined. The device presented a reliable behavior and good reproducibility even under influence of external parameters like light and magnetic fields.